PENGELOLAAN BUMDES DALAM MENINGKATKAN EKONOMI MASYARAKAT DI DESA LUWOO KECAMATAN TELAGA JAYA KABUPATEN GORONTALO - Joice Machmud; Umar Sako Baderan; Ismail Azis (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2018)
This research aims to determine and describe the management of BUMDes in improving the community's economy in Luwoo Village, Telaga Jaya District, Gorontalo Regency. Data analysis method used is qualitative data analysis carried out interactively and continuously until it is complete, so that the data is already saturated. Data obtained from interviews with the Chairman of BUMDes Tumulo, other BUMDes management and the local community as business unit actors who can provide information in connection with the problem being examined. The results showed that the management of BUMdes in improving the economy of the community in Luwoo Village, Telaga Jaya District, Gorontalo Regency was seen from the management principles of cooperative, participatory, emancipatory, transparent, accountable, and sufficiency, so it still needed improvement and further improvement from all fields. Especially in terms of coordination in ordering goods with the distributor so that there are no more delays in the delivery of the goods, lack of inventory and the stock of goods.